Access to the administrative contentious jurisdiction - Ledesma Narvaez, Marianella (2020)
In classical terms, the administrative-adversary jurisdiction is aimed at hearing all claims filed by claimants against acts of the government administration subject to Administrative Law. However, this traditional concept has been superseded in favor of conceiving it as a channel for a true and suitable effective jurisdictional protection of the legitimate rights and interests of citizens facing any unlawful act committed by the government administration. This fact has produced an increase in the transfer of discussion from the administrative venue to the judicial venue, since adversary proceedings do not refer to administrative acts nor are they conditioned to the contents of said acts and consequently, the center of gravity in the administrative adversary dispute is no longer the administrative act itself but the subjective interests of the citizens that confront the government administration